Professional development for language teachers : - Richards, Jack C. (Cambridge University Press, 2005)
This much-needed text provides a coherent and strategic approach to teacher development Teacher Development for Language Teachers examines ten different approaches for facilitating professional development in language teaching: self-monitoring, support groups, journal writing, classroom observation, teaching portfolios, analysis of critical incidents, case analysis, peer coaching, team teaching, and action research. The introductory chapter provides a conceptual framework. All chapters contain practical examples and reflection questions to help readers apply the approach in their own teaching context.